2011
DOI: 10.2215/cjn.00470111
|View full text |Cite
|
Sign up to set email alerts
|

GFR Decline and Mortality Risk among Patients with Chronic Kidney Disease

Abstract: SummaryBackground and objectives Estimates of the effect of estimated GFR (eGFR) decline on mortality have focused on populations with normal kidney function, or have included limited information on factors previously shown to influence the risk of death among patients with CKD.Design, setting, participants, & measurements We retrospectively assessed the effect of rate of eGFR decline on survival of patients with CKD receiving primary care through a large integrated health care system in central Pennsylvania b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
118
1
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(138 citation statements)
references
References 18 publications
13
118
1
1
Order By: Relevance
“…Alternatively, an antecedent decline in true GFR may simply reflect a more severe comorbidity profile. 12,14 For example, although we adjusted for diabetes and our findings were qualitatively similar after excluding subjects with diabetes, we did not adjust for severity of diabetes, a key determinant of both true GFR decline and mortality risk. 21,22 Similarly, episodes of acute coronary syndrome or congestive heart failure may increase the risk of death and also, cause true GFR decline.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Alternatively, an antecedent decline in true GFR may simply reflect a more severe comorbidity profile. 12,14 For example, although we adjusted for diabetes and our findings were qualitatively similar after excluding subjects with diabetes, we did not adjust for severity of diabetes, a key determinant of both true GFR decline and mortality risk. 21,22 Similarly, episodes of acute coronary syndrome or congestive heart failure may increase the risk of death and also, cause true GFR decline.…”
Section: Discussionmentioning
confidence: 81%
“…Similar to previous work, in which adjustments were made for either the first or last eGFR in the antecedent period, we found a U-shaped relationship between eGFR slope and subsequent ACM risk. 11,[13][14][15][16] Direct, quantitative comparison between the results of these investigations and our own investigations are hampered by different indices of renal function change, different antecedent periods, and the use of rates, in some studies, rather than HRs to quantify mortality risk. However, Turin et al 12 found adjusted HRs for ACM of 1.14 and 1.68 for 4-ml/min per 1.73 m 2 per year declining and increasing slopes, respectively, compared with subjects with a stable eGFR value in a Canadian population-based study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 The mortality rate in ESKD patients maintained on dialysis is striking, with a life expectancy less than one-third that of their counterparts without ESKD, and a 5-year survival rate on dialysis of only 40%. 6 There is also a substantial healthcare cost associated with provision of ESKD care, currently estimated at $33 billion annually in the US, ABSTRACT equating to 6.3% of the Medicare Budget.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Even in its early stages, CKD is associated with accelerated cardiovascular disease and increased mortality, with an exponential increase in attributable risk as GFR declines to end-stage kidney disease (ESKD). 4,5 The mortality rate in ESKD patients maintained on dialysis is striking, with a life expectancy less than one-third that of their counterparts without ESKD, and a 5-year survival rate on dialysis of only 40%. 6 There is also a substantial healthcare cost associated with provision of ESKD care, currently estimated at $33 billion annually in the US,…”
Section: Introductionmentioning
confidence: 99%